KORELASI USIA PERNIKAHAN DINI PADA IBU TERHADAP KEJADIAN STUNTING - Mauludiyah, Zaida; Utami, Utami; Cahyani, Desy Dwi; Muzayyana, Muzayyana (Ensiklopedia of Journal, 2025)
Abstract: Early marriage is still one of the social problems that is quite complex and continues to occur in various parts of the world. Early marriage can potentially have LBW children and even stunting. The purpose of the study was to determine the correlation of early marriage age in mothers to the incidence of stunting. The research design used in this study was cross sectional. The research was conducted in Banggae District in June 2024. The population in this study were all married mothers in the working area of Banggae District. The sample amounted to 82 respondents. The sampling technique used in this study was Simple Random Sampling. Data analysis was done univariate and bivariate. The results showed no relationship between the age of early marriage (p value: 0.675). It is recommended that the health center provide education about the right age for marriage in adolescents and provide motivation to pursue higher education.Keywords: Toddlers, Early Marriage, Stunting.